-66=-3(m+5)

Simple and best practice solution for -66=-3(m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -66=-3(m+5) equation:



-66=-3(m+5)
We move all terms to the left:
-66-(-3(m+5))=0
We calculate terms in parentheses: -(-3(m+5)), so:
-3(m+5)
We multiply parentheses
-3m-15
Back to the equation:
-(-3m-15)
We get rid of parentheses
3m+15-66=0
We add all the numbers together, and all the variables
3m-51=0
We move all terms containing m to the left, all other terms to the right
3m=51
m=51/3
m=17

See similar equations:

| 15=-5t^2+20t+1 | | 4(-x+2)=x-5+3 | | 5b+5=14+2b | | -3/7h=42 | | 5(2t-3)-7.5t=0.5(12-0) | | x=8,2x-10 | | -9(-6+b)=135 | | 30-n=59 | | -10(n+1)=60 | | 296-3x=444-5x | | -8=-29-n | | 14=g+5 | | 24=g+5 | | 21/27=x/8 | | -14=1-x | | 2=3+x/6 | | 26(h-948)=780 | | -1/3p=2 | | (0.4+g)÷1=5.4 | | (7+0.5)-b=2.9 | | 17(g-926)=323 | | -1.4m=-2.1 | | 931=19(m+34) | | 27(t+4)=999 | | -67=10-7p | | 23(v+3)=782 | | 37=n+23 | | 2x+2(-2)=10x-4 | | (h*1)÷2.5=0.8 | | 9(u-891)=315 | | k-355/13=30 | | 32m=624m= |

Equations solver categories